Co-production and Criminal Justice - Johns, Diana; Spivakovsky, Claire; Flynn, Catherine; Turner, Shelley; Hall, Maggie (Routledge, 2022)
This book explores practical examples of co-production in criminal justice research and practice. Through a series of seven case studies, the authors examine what people do when they co-produce knowledge in criminal justice contexts: in prisons and youth detention centres; with criminalised women; from practitioners' perspectives; and with First Nations communities.